Bioinspired multifunctional adhesive system for next generation bio-additively designed dental restorations. (January 2021) - Sarikaya, Rizacan; Song, Linyong; Yuca, Esra; Xie, Sheng-Xue; Boone, Kyle; Misra, Anil; Spencer, Paulette; Tamerler, Candan
Abstract: Resin-based composite has overtaken dental amalgam as the most popular material for the repair of lost or damaged tooth structure. In spite of the popularity, the average composite lifetime is about half that of amalgam restorations. The leading cause of composite-restoration failure is decay at the margin where the adhesive is applied. The adhesive is intended to seal the composite/tooth interface, but the adhesive seal to dentin is fragile and readily degraded by acids, enzymes and other oral fluids. The inherent weakness of this material system is attributable to several factors including the lack of antimicrobial properties, remineralization capabilities and durable mechanical performance ― elements that are central to the integrity of the adhesive/dentin (a/d) interfacial seal. Our approach to this problem offers a transition from a hybrid to a biohybrid structure. Discrete peptides are tethered to polymers to provide multi-bio-functional adhesive formulations that simultaneously achieve antimicrobial and remineralization properties. The bio-additive materials design combines several functional properties with the goal of providing an adhesive that will serve as a durable barrier to recurrent decay at the composite/tooth interface. This article provides an overview of our multi-faceted approach which uses peptides tethered to polymers and new polymer chemistries to achieve the next generation adhesive system ― an adhesive that provides antimicrobial properties, repair of defective dentin and enhanced mechanical performance.